2021
DOI: 10.3389/fninf.2021.720229
|View full text |Cite
|
Sign up to set email alerts
|

A Toolbox and Crowdsourcing Platform for Automatic Labeling of Independent Components in Electroencephalography

Abstract: Independent Component Analysis (ICA) is a conventional approach to exclude non-brain signals such as eye movements and muscle artifacts from electroencephalography (EEG). A rejection of independent components (ICs) is usually performed in semiautomatic mode and requires experts’ involvement. As also revealed by our study, experts’ opinions about the nature of a component often disagree, highlighting the need to develop a robust and sustainable automatic system for EEG ICs classification. The current article pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Specifically, MARA indicated that the ICA results always improved with more cleaning because MARA quantifies only the probability of a component containing an artifact, not the probability of a component being brain-like. Meanwhile, metrics such as ICLabel and ALICE [ 37 ] attempt to also label brain-like components. We decided to use ICLabel as our main component labeling method, combined with residual variance (from dipole fitting).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, MARA indicated that the ICA results always improved with more cleaning because MARA quantifies only the probability of a component containing an artifact, not the probability of a component being brain-like. Meanwhile, metrics such as ICLabel and ALICE [ 37 ] attempt to also label brain-like components. We decided to use ICLabel as our main component labeling method, combined with residual variance (from dipole fitting).…”
Section: Discussionmentioning
confidence: 99%
“…This would provide important information regarding the situations in which different methods should be used. Finally, other recent component labeling algorithms such as ALICE [ 37 ] can be introduced when comparing different cleaning approaches to limit bias.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed EEG fragment 1756 s of eyes open condition for the patient and 1550–2000 s of eyes open condition for each child of the control group (1803 ± 79 s). Independent component analysis (ICA) was used when needed to subtract the most evident artifacts [ 20 ]. The three separate neurologists (including GP) with expert certification identified and interpreted the EEG data, reaching common decisions.…”
Section: Methodsmentioning
confidence: 99%
“…Bad channel interpolation was applied when necessary (0-2 channels per participant). Automatic raw data inspection with ± 400µV thresholds was used for rejecting EEG segments with large artifacts, then for artifact rejection, the independent component analysis (ICA) was performed, in particular the ALICE platform was used [19]. The data were segmented into epochs starting 200 ms before a stimuli onset and lasting 500 ms after the onset.…”
Section: Data Processingmentioning
confidence: 99%